Co-delivery of doxorubicin and P-gp inhibitor by a reduction-sensitive liposome to overcome multidrug resistance, enhance anti-tumor efficiency and reduce toxicity. (3rd May 2016) - Tang, Jie; Zhang, Li; Gao, Huile; Liu, Yayuan; Zhang, Qianyu; Ran, Rui; Zhang, Zhirong; He, Qin
Abstract: To overcome multidrug resistance (MDR) in cancer chemotherapy with high efficiency and safety, a reduction-sensitive liposome (CL-R8-LP), which was co-modified with reduction-sensitive cleavable PEG and octaarginine (R8) to increase the tumor accumulation, cellular uptake and lysosome escape, was applied to co-encapsulate doxorubicin (DOX) and a P-glycoprotein (P-gp) inhibitor of verapamil (VER) in this study. The encapsulation efficiency (EE) of DOX and VER in the binary-drug loaded CL-R8-LP (DOX + VER) was about 95 and 70% (w/w), respectively. The uptake efficiencies, the cytotoxicity, and the apoptosis and necrosis-inducing efficiency of CL-R8-LP (DOX + VER) were much higher than those of DOX and the other control liposomes in MCF-7/ADR cells or tumor spheroids. Besides, CL-R8-LP (DOX + VER) was proven to be uptaken into MCF-7/ADR cells by clathrin-mediated and macropinocytosis-mediated endocytosis, followed by efficient lysosomal escape. In vivo, CL-R8-LP (DOX + VER) effectively inhibited the growth of MCF-7/ADR tumor and reduce the toxicity of DOX and VER, which could be ascribed to increased accumulation of drugs in drug-resistant tumor cells and reduced distribution in normal tissues. In summary, the co-delivery of chemotherapeutics and P-gp inhibitors by our reduction-sensitive liposome was a promising approach to overcome MDR, improve anti-tumor effect and reduce the toxicity of chemotherapy.